Scheduling restaurant staff using integer programming in cooperation with Matur og drykkur - Inga María Backman 1987- (2020)
Running a restaurant in Iceland can be a challenging task, and the greatest challenge is without a doubt the cost of maintaining a staff. Restaurants are often run with a low margin of profit, as the overall operational costs can be high. Shift managers spend tremendous amounts of time manually organizing a schedule each month. It is, however, not always in the business’ economic best interests to honor staff members’ every request and preference. This thesis presents a model that helps the shift manager set up a staff schedule. It is written in collaboration with the restaurant Matur og Drykkur, situated at Grandagarður in Reykjavík. Like many restaurants, the management of Matur og Drykkur wants a better solution for staff scheduling, and to take a better look at opening hours in relation to staff cost. Matur og Drykkur fully cooperates in sharing information and providing the data necessary to create this model. The main goal of the thesis is to create a mathematical model that minimizes the restaurant’s cost while carefully considering equality among the staff, respect for the owners’ demands, as well as compliance with union rules. This mathematical model ensures staff satisfaction, minimizes operational costs, and relieves the shift manager of the burden of manually preparing shift schedules. Keywords: Optimization, restaurant industry, scheduling Að reka veitingastað á Íslandi er krefjandi verkefni. Veitingastaðir eru oftar en ekki reknir með litlum hagnaði þar sem það er kostnaðarsamt að reka veitingastað, en þar spilar starfsmannakostnaður eitt stærsta hlutverkið. Vaktstjórar eyða ómældum tíma í að útbúa vaktaplan handvirkt í hverjum mánuði. Þeir hafa í huga starfsmanna óskir um vaktafrí en gleyma oft hvað gæti verið hagkvæmast fyrir rekstur fyrirtækisins. Meginmarkmið með þessari ritgerð er að útbúa stærðfræðilíkan sem lágmarkar kostnað fyrirtækisins en hefur á sama tíma þarfir starfsmanna í huga sem og kjarasamninga og réttindi sem fara þarf eftir. Á þennan hátt mun módelið sjá til þess að kostnaður ...